14+3(5t-12)=1-(20t+1)

Simple and best practice solution for 14+3(5t-12)=1-(20t+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14+3(5t-12)=1-(20t+1) equation:



14+3(5t-12)=1-(20t+1)
We move all terms to the left:
14+3(5t-12)-(1-(20t+1))=0
We multiply parentheses
15t-(1-(20t+1))-36+14=0
We calculate terms in parentheses: -(1-(20t+1)), so:
1-(20t+1)
determiningTheFunctionDomain -(20t+1)+1
We get rid of parentheses
-20t-1+1
We add all the numbers together, and all the variables
-20t
Back to the equation:
-(-20t)
We add all the numbers together, and all the variables
15t-(-20t)-22=0
We get rid of parentheses
15t+20t-22=0
We add all the numbers together, and all the variables
35t-22=0
We move all terms containing t to the left, all other terms to the right
35t=22
t=22/35
t=22/35

See similar equations:

| 6+6y-15=39 | | (3x5^2/15)-(5-2^2)=0 | | 72=-9xX2 | | 14=c2+ 12 | | (2/3)w-1/2=1/4 | | y+3=2y+4 | | -2j+16.52=2.52 | | 9+b/4=7 | | -11(x+26)-27(x+26)=15x-15 | | 3x+-8=15 | | 6=j2− –4 | | 2x-8x-13=6x+5-13 | | 7.5x+30=x | | j/4+27=35 | | -5+2x/5=5 | | 8x+4x=-15-9 | | 5.6➗0.4-r=-8 | | -6+2x/5=0 | | -2d+-8.09=-1.85 | | 2(x-1)/3=2(x+5)/9 | | 2m-31=23 | | 2/3(3x-9)=-2(2x+6) | | 7h-10=67 | | 72=−9x2 | | 10=-8-50+3y | | 6f+9=51 | | 86=-7a+2 | | 3.2/12.6=g | | 86=−7a+2 | | 48=6(f+2) | | -4.3-14.5=n | | 6(x-1)/40=3(x+2)/40 |

Equations solver categories